Lasioderma serricorne (Coleoptera: Anobiidae) in Stored Matricaria recutita (Asteraceae) in Brazil - Zanuncio, José Cola; Tavares, Wagner De Souza; Faroni, Lêda Rita D'Antonino; Wilcken, Carlos Frederico [UNESP]; Serrão, José Eduardo (My University, 2014)
Insects pests of stored products and by-products are extending their feeding preferences to new items. We report for the first time in Brazil the feeding and reproduction of the cigarette beetle, Lasioderma serricorne F. (Coleoptera: Anobiidae) on stored chamomile, Matricaria recutita L. (Asteraceae). One intact package (10 cm wide × 15 cm long) of M. recutita infested by L. serricorne was purchased in a supermarket in Viçosa, Minas Gerais, Brazil. In this sample this insect had fed on the dried parts (inflorescences and rods), which made the product unfit for human consumption. This 20 g sample included 101 live and 4 dead Lasioderma serricorne. Circumstantial evidence suggested that the infested material was probably harvested from an infested field in Apr 2013 and packaged with L. serricorne eggs, and that these had developed into the adults found in the package.
Keywords: Asterales; Bostrichiformia; Bostrichoidea; chamomile; medicinal plant